Strategi Komunikasi Walikota Payakumbuh dalam Program Ruang Informasi dan Dialog (RIDA) Bersama Warga Payakumbuh - Rayuni Rayuni; Muhammad Fajri (STIKes Ibnu Sina Ajibarang, 2024)
The Ruang Informasi dan Dialog Bersama (RIDA) Program in Payakumbuh City is a government initiative that facilitates dialogue and information exchange between the city government and its residents. RIDA helps monitor government performance, promotes accountability, and encourages transparency. Through active dialogue, the program generates creative ideas and innovative solutions to complex issues, enabling community participation in problem-solving. RIDA also strengthens the trust relationship between the community and the government. The communication strategy of this program aims to achieve desired changes in behavior, understanding, or specific conditions. RIDA enables residents to communicate with the government through Zoom, eliminating the need to visit the government office in person, making it easier to convey complaints or suggestions directly to the mayor. This research also explores the communication strategy of the Mayor of Payakumbuh within RIDA, identifying elements such as messages, communicators, recipients, target audiences, media used, effects produced, and barriers in the RIDA program process.